Sudden motor and sensorial loss due to retroperitoneal hematoma during postoperative periods: a case report - Şen,Pelin (2017)
Abstract A 68 year-old male patient was hospitalized for radical prostatectomy. He had no abnormal medical history including neurological deficit before the operation. Prior to general anesthesia, an epidural catheter was inserted in the L3-4 interspace for intraoperative and postoperative analgesia. After surgery for nine hours, he developed confusion and flaccid paralysis of bilateral lower extremities occurred. No pathology was detected from cranial computed tomography and diffusion magnetic resonance imaging no pathology was detected. His thoracic/lumbar magnetic resonance imaging. Intraabdominal pressure was shown to be 25 mmHg, and abdominal ultrasonography revealed progression in the inflammation/edema/hematoma in the perirenal region. The Bromage score was back to 1 in the right foot on the 24th hour and in the left foot on the 26th hour. Paraplegia developed in patients after epidural infusion might be caused by potentiated local anesthetic effect due to retroperitoneal hematoma and/or elevated intra-abdominal pressure.